PENINGKATAN KETERAMPILAN MEDIA SOSIAL MELALUI PELATIHAN DIGITAL MARKETING PADA PELAKU UMKM “ACHI CRAFT GALERY” DI KECAMATAN KURANJI KOTA PADANG - Marta, Revi; Suwandi, Rifki; Havifi, Ilham (Jurnal Hilirisasi IPTEKS, 2024)
The digital marketing training for “Achi Craft Galery” MSME players in Kuranji District, Padang City, aims to improve skills in digital marketing, especially through social media and packaging design. MSME players face significant challenges in the form of a lack of understanding of modern marketing strategies and limitations in utilizing digital technology, which has an impact on product sales. The activity methods include intensive training using the Canva graphic design platform, focus group discussion (FGD) sessions to identify marketing problems, and assistance in implementing digital marketing strategies. The targets of the activities included 6 MSME partners with various business fields under “Achi Craft Galery”. The results of the activity showed an increase in participants' skills in promotional design, understanding of social media algorithms, and the ability to develop digital marketing strategies. Participants were able to create attractive and informative flyer designs, improve product packaging quality, and utilize social media and e-commerce platforms such as Tokopedia and Instagram Shopping to expand the market. FGD sessions helped participants overcome technical and operational obstacles in digital marketing. The conclusion of this activity is that the training succeeded in increasing the competitiveness of MSMEs in the dynamic digital economy era. This success is reflected in the improvement of participants' technical skills, expansion of market access, and improvement of marketing quality. The program also has the potential to create sustainability through long-term development based on digital technology. Further assistance to support the implementation and development of marketing strategies is recommended.